KAJIAN PENERAPAN MATRIKS DALAM KEHIDUPAN SEHARI-HARI UNTUK MENINGKATKAN MOTIVASI BELAJAR: A Literature Review on the Application of Matrices in Daily Life to Enhance Learning Motivation - Yahya, Muhammad Hamdi; Raharjo, Karunia; Ammarulloh, Satriaji; Putri, Adhysta Az-zahra; Himawan, Inggil (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2025)
This article is a literature review aimed at analyzing how the application of matrix concepts in real-life contexts can influence students’ motivation to learn mathematics. The main issue addressed is the lack of student interest due to the abstract nature of matrix material, which is often disconnected from their daily experiences. To address this, the study synthesizes findings from previous academic works and analyzes the effectiveness of contextual approaches in mathematics education. The review reveals that learning strategies such as Problem-Based Learning (PBL), Realistic Mathematics Education (PMRI), and Contextual Teaching and Learning (CTL) significantly enhance students' conceptual understanding and engagement. When matrix concepts are presented through familiar situation such as scheduling, task allocation, or simple data processing students become more confident, involved, and interested in learning. In conclusion, aligning mathematical content with everyday experiences provides a more relevant and enjoyable learning process that fosters stronger learning motivation and a better appreciation for the practical use of mathematics.